EFFECT OF RISK MANAGEMENT ON FINANCIAL PERFORMANCE OF SERVICE COMPANIES IN Mogadishu, SOMALIA - Wehelie, Abdi Mohamed; Mukhongo, Aaron L. (IJRDO - Journal of Business Management, 2017)
The general objective of this study was to investigate the effect of risk management on financial performance of service companies in Mogadishu, Somalia. Specifically, this study investigated the effect of credit risk, liquidity risk, market risk and foreign risk management on the financial performance of service companies in Mogadishu, Somalia. Effect of risk management practices has been vital in allowing the phenomenal growth in service companies. The operators of small, medium and large Scale businesses face certain degree of risk in their daily operation globally. Service companies were only succeed if their financial performances are made well In order to ensure the importance of financial performances for service companies and its determinants play the effectiveness and efficiency in service companies. Risk management should, therefore, be at the core of any organization this involves identifying and analysing risks, developing and implementing risk handling techniques and monitoring the progress of these in order to avoid and/or reduce the impact of risk on the financial performance of the firms. The population of the study was 167 a sample size of 50 Respondents selected which composed of management and staff in service companies in Mogadishu Somalia. inexperience in the field of business, particularly lack of technical knowledge plus inadequate managerial skills, lack of planning and lack of market research as causes of big business failure.. The sampling procedure of this study was used non-probability sampling procedure particularly. The study was used descriptive crosssectional such us descriptive survey and explanatory research design and analytical based on quantitative data both primary and secondary sources based on the scope of the study. This research employed both qualitative and quantitative data collection method whereby data were gathered by the use of closed ended questionnaires which are self-administered. The data collection was analysed using the software called Statistical Package for the Social Sciences (SPSS) version20. Factor analysis was used to assess the validity and Cronbach alpha to assess reliability of the questionnaire. Multiple regression analysis (standard and step wise) were conducted to determine the relationship between the effects of risk management determinants and financial performance. Results confirm the varying importance of the risk management determinants in the service companies in Somalia. In general, the results revealed that market risk, credit risk and liquidity risk have significant and positive effects on financial performance, while foreign exchange risk has insignificant effects on financial performance in the service companies in Somalia. The study findings indicated that there was a strong positive relationship (R= 0.720) between the variables. Standard multiple regression was conducted and there was positive and significant effect of Market risk on financial performance. On the standard multiple regression, there was positive and significant effects of Credit risk management on financial performance, there was positive and significant effects of liquidity risk on financial performance and there was positive but insignificant effects of Foreign exchange rate on financial performance .The study also recommends that the management of service companies should continuously assess their risk management practices to see if they are still practical in the face of a continuously changing operating environment. This will ensure that Somali service companies achieve international standards and, therefore, become both locally globally competitive